The Effect of Murrotal Therapy With St Belt on Maternal and Fetal Wellbeing - Tri Sunarsih; Ekawati Ekawati; Endah Puji Astuti; Elvika Fit Ari Shanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Background. Improving fetal intelligence starts with stimulation made by his mother; maternal soul tranquility highly affects the stimulation a mother will make to her fetus. Maternal soul tranquility will make the mother stimulate her baby happily, thereby improving fetal intelligence. For pregnant women to be able to stimulate the fetus well, they should be healthy physically, mentally, spiritually, and socially. Objective. This research aims to find out the effect of St Belt on maternal and fetal spiritual well-being. Method. This research used a quasi-experimental method. The design used was a non-equivalent pre-test and post-test control-group design. The population of the research was all pregnant women with 24-38 week gestation having their pregnancy examined routinely in PMB Kuswatiningsih. The sampling technique used in this research was nonprobability sampling with purposive sampling. The main instruments used were Spiritual Well-Being and CTG. Data analysis was conducted using paired and independent t-tests. Result. There is no difference in breath movement, DJJ, and amniotic fluid volume between before and after intervention in the experimental group. There are 8 (eight) pregnant women with a score of 10, 1 (one) with a score of 8, and 1 (one) with a score of 6. In the control group, there is a difference in scores; in the prior examinations, 6 (six) pregnant women scored 10, but in the last examination, 7 pregnant women scored 10. There is a significant difference of anxiety levels after intervention in the respondents in the experimental group with a p-value = 0.002 (p less than 0.50). There is a significant difference in the spiritual level before intervention in the respondents of the experimental group with a p-value = 0.002 (p less than 0.50).